2013
DOI: 10.3109/14767058.2013.815718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal exposure to phthalates and bisphenol A during pregnancy on gestational age

Abstract: Objective Phthalates and bisphenol A (BPA) are ubiquitous environmental toxicants, present in high concentrations in numerous consumer products. We hypothesized that maternal exposure to phthalates and BPA in pregnancy is associated with shortened gestation. Methods Urinary phthalate and BPA metabolites from 72 pregnant women were measured at the last obstetric clinic visit prior to delivery. Using linear regression models, we estimated the change in gestational age associated with each interquartile range (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 30 publications
2
67
1
Order By: Relevance
“…However, among females in the present study, ΣDBP levels earlier in pregnancy were associated with decreased birth weight. In contrast to previous studies (13,18-20,24), DEHP metabolites measured during the first trimester or at delivery were not associated with size or gestational age at birth. Our findings are also inconsistent with a case-control study performed in France which found no significant associations between prenatal phthalate metabolite levels and birth outcomes (16), however, this study was different from the current analysis in many aspects, including study population, design, and standardization of phthalate levels that could potentially explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, among females in the present study, ΣDBP levels earlier in pregnancy were associated with decreased birth weight. In contrast to previous studies (13,18-20,24), DEHP metabolites measured during the first trimester or at delivery were not associated with size or gestational age at birth. Our findings are also inconsistent with a case-control study performed in France which found no significant associations between prenatal phthalate metabolite levels and birth outcomes (16), however, this study was different from the current analysis in many aspects, including study population, design, and standardization of phthalate levels that could potentially explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Phthalate and BPA exposure among pregnant women have been associated with altered hormone levels (8,55,56), increased oxidative stress during pregnancy (49,57), and birth outcomes such as low birth weight (18,27) and decreased gestational age (20). However, entering concurrently measured phthalate metabolite and BPA levels into regression models together did not alter our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously examined the relationship between cord blood concentrations of NIS inhibitors and newborn size among a sample of healthy mothers with full-term pregnancies [23]. In that study, we did not observe trends of decreasing newborn weight, length, or head circumference across increasing quartiles of cord blood perchlorate, thiocyanate, nitrate, or PEC.…”
Section: Discussionmentioning
confidence: 86%
“…The study population and protocol for this study have been described previously [23]. Briefly, we recruited 107 pregnant women (9–39 weeks gestation at enrollment) between December 2008 and July 2010 from the High-Risk Obstetric Clinic at Robert Wood Johnson University Hospital.…”
Section: Methodsmentioning
confidence: 99%